Teacher Perceptions of Behavior Problems in Small and Large Schools - Ruth E. Marin; Patricia Walford-Kraemer; Harriet K. Light (Journal of Research in Rural Education, 1983)
A total of 144 teachers from rural and urban schools in a midwestern state responded to open-ended questions related to students' behavior problems. Differences between students from rural and urban schools are described in the areas of serious behavior problems, handling behavior problems, and eliminating behavior problems.